Associations of road traffic noise with adipose tissue depots and hepatic fat content – Results from the German National Cohort (NAKO) - Fiona Niedermayer; Susanne Rospleszcz; Clara Matthiessen; Barbara Hoffmann; Sophia Stoecklein; Tobias Haueise; Tobias Norajitra; Christopher L. Schlett; Johanna Nattenmüller; Fabian Bamberg; Jürgen Machann; Matthias Günther; et al. (Environment International)
Little is known about the relation between traffic noise exposure, an established environmental risk factor for cardiovascular disease, and early obesity-related risk markers such as adipose tissue (AT) and hepatic fat. Therefore, we aimed to assess associations of long-term road traffic noise exposure with AT depots measures from whole-body magnetic resonance imaging (MRI). We analyzed cross-sectional data from 11,343 participants from the population-based German National Cohort (NAKO) who underwent MRI examination between 2014 and 2016, considering visceral (VAT), subcutaneous abdominal (SCAAT), subcutaneous thoracic AT (SCTAT) and hepatic fat content as outcomes. Annual road traffic noise (Lden) data from the year 2017 (source: central EIONET data repository) was used to calculate weighted mean noise levels on a continuous scale within 10 and 100-meter buffers of participants’ residencies. Among 11,101 participants with complete outcome data, 48.7 % were women, and the mean age was 51.9 years. Higher annual Lden was associated with increased AT depots and hepatic fat content in men (e.g., VAT: 1.72 %-change [95 % confidence interval: [0.14 %; 3.30 %]; SCAAT: 2.18 %-change [0.43 %; 3.93 %], hepatic fat content: 3.57 %-change [1.41 %; 5.78 %] per 10 dB(A) increase in Lden (10 m)) and women (e.g., VAT: 3.13 %-change [1.09 %; 5.18 %]; SCAAT: 2.38 %-change [0.55 %; 4.20 %], hepatic fat content: 3.08 %-change [1.00 %; 5.21 %] per 10 dB(A) increase in Lden (10 m)). Associations were robust with all outcomes after adjusting for air pollutants and surrounding greenness, and effect modification by obesity and hypertension was observed for SCAAT, SCTAT and hepatic fat content. Our findings indicate that annual exposure to road traffic noise is associated with increased adipose tissue depots and hepatic fat content, and thus present novel evidence for the cross-sectional association between noise and early MRI-derived metabolic health markers.